Dampak Fluktuasi Nilai Tukar Terhadap Laporan Keuangan Konsolidasi : Studi Kasus PT. Mayora Indah Tbk - Dina Nur Ayifa; Ulfa Ulfa; M. Masrukhan (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
This study aims to assess the impact of exchange rate fluctuations on the consolidated statements of PT Mayora Indah Tbk. At PT Mayora Indah Tbk, exchange rate fluctuations have a major influence on financial statements, this can happen because of the influence of global commodity prices where subsidiaries are located abroad, third party cooperation for export sales, loans and also the cost of purchasing the main raw materials for the company's production. The method used in this research is qualitative research, where the object of research is PT Mayora Indah Tbk. Collecting data and information using library research methods and PT Mayora Indah Tbk data taken from the annual consolidated financial statements of PT Mayora Indah Tbk. The results showed that the treatment of foreign exchange and foreign currency differences at PT Mayora Indah Tbk, is in accordance with the applicable PSAK.